Future Time Perspective and Frustration Intolerance in Medical students - Areeb Khalid, Hafiz Tanveer Tariq , Muhammad Umar Afzal, Abdur Rehman Malik, Adam Umair Ashraf Butt, Areeb Khalid, Hafiz Tanveer Tariq , Muhammad Umar Afzal, Abdur Rehman Malik, Adam Umair Ashraf Butt (Journal of Rawalpindi Medical College, 2021)
Background: The future perception of students is affected by a series of events happening throughout their course of studies. The objective of this study is to measure the Future time perspective (FTP) and Future intolerance (FI) among medical students during the COVID-19 lockdown. Materials and Methods: It was a descriptive cross-sectional study done from January 15, 2020 to July 20, 2020 among MBBS students of Rawalpindi Medical University. The questionnaire consisted of 1) Socio-demographic details, 2) Future Time Perspective scale, and 3) Frustration Discomfort scale. An online survey was done using Google Forms. An ANOVA was run to check for differences in FTP and FI between the classes. Bivariate analysis for continuous variables was applied. The data were analysed using the Statistical Package for Social Sciences (SPSS) v.23.0 (IBM, Armonk, US). Results: Mean age of participants was 21.8 (SD=1.66) with majority females 331(58.4%). The mean FTP score and mean FI scores were 50.8(SD=19.43) and 91.46(SD=17.65) respectively. Final-year students had the highest mean score (Mean=57.94(SD=7.72)) for FI. On the other hand, mean scores for FDS were highest in first-year students (Mean=102.89 (SD=13.52)) while lowest in fourth-year students (Mean=81.73(SD=17.49)) with P=.005. There was a significant difference in the dimensions of Emotional Intolerance and achievement among females and males. Bivariate analysis showed a significant negative correlation was found between FTP and the dimension of discomfort intolerance (r = -0.158, p < 0.001), while a significant positive correlation was found between FTP and the dimension of achievement (r = 0.225, p < 0.001). Conclusion: Our study concludes that final-year students have a much higher tolerance level for adversities. Furthermore, they also have a much more positive perspective and a clearer vision regarding their future.